Demonstration of novel gain‐of‐function mutations of αIIbβ3: association with macrothrombocytopenia and glanzmann thrombasthenia‐like phenotype. Issue 2 (22nd April 2013) - Kashiwagi, Hirokazu; Kunishima, Shinji; Kiyomizu, Kazunobu; Amano, Yoshiro; Shimada, Hiroyuki; Morishita, Masashi; Kanakura, Yuzuru; Tomiyama, Yoshiaki
Abstract Integrin αIIbβ3 is indispensable for normal hemostasis, but its role for thrombopoiesis is still controversial. Recently, αIIb and β3 mutations have been identified in patients with congenital macrothrombocytopenia. We analyzed three unrelated Japanese families with congenital macrothrombocytopenia. Expression and activation state of αIIbβ3 in platelets was examined by flow cytometry and immunoblotting. Sequence of whole coding region and exon–intron boundaries of ITGA2B and ITGB3 genes was performed. The effects of mutations on αIIbβ3 activation state and phosphorylation of FAK were analyzed in transfected cells. We newly identified three mutations: two mutations in highly conserved Gly‐Phe‐Phe‐Lys‐Arg sequence in juxtamembrane region of αIIb, p.Gly991Cys and p.Phe993del, and one donor site mutation of intron 13 of ITGB3 leading to 40 amino acids deletion, p.(Asp621_Glu660del), in the membrane proximal β‐tail domain of β3. One patient, who showed Glanzmann thrombasthenia‐like marked reduction in surface αIIbβ3 expression (3–11% of normal control), was a compound heterozygote with ITGA2B p.Gly991Cys and a novel nonsense mutation, ITGA2B p.Arg422*. All three mutations, ITGA2B p.Gly991Cys, ITGA2B p.Phe993del, and ITGB3 p.(Asp621_Glu660del), led to highly activated conformation of αIIbβ3 and spontaneous tyrosine phosphorylation of FAK in transfected cells. These results suggest that gain‐of‐function mutations around membrane region of αIIbβ3 lead to abnormal platelet number and morphology with impaired surface αIIbβ3 expression.